2018
DOI: 10.3389/fpls.2018.00992
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Three Irrigation Strategies on Gas Exchange Relationships, Plant Water Status, Yield Components and Water Productivity on Grafted Carménère Grapevines

Abstract: In the Chilean viticultural industry, Carménère is considered an emblematic cultivar that is cultivated mainly in arid and semi-arid zones. For this reason, it is necessary to use precise irrigation scheduling for improving water use efficiency (WUE), water productivity (WP), yield and wine quality. This study evaluated the effects of three deficit irrigation strategies on gas exchange variables, WUE, WP and yield components in a drip-irrigated Carménère vineyard growing under semi-arid climatic conditions dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 61 publications
(106 reference statements)
3
9
0
Order By: Relevance
“…These values agree with WP values in other studies of 2.4 kg m −3 (Texeira et al 2009) and 3.4 kg m −3(Atroosh et al 2013), whereas a study in Chile reported WP values of 4.1-7.3 kg m −3 depending on the irrigation strategy employed(Zuñiga et al 2018). However, this wide variability in the reported WP values is strongly influenced by differences in canopy management and cluster thinning, environmental conditions and rootstock variety.…”
supporting
confidence: 91%
“…These values agree with WP values in other studies of 2.4 kg m −3 (Texeira et al 2009) and 3.4 kg m −3(Atroosh et al 2013), whereas a study in Chile reported WP values of 4.1-7.3 kg m −3 depending on the irrigation strategy employed(Zuñiga et al 2018). However, this wide variability in the reported WP values is strongly influenced by differences in canopy management and cluster thinning, environmental conditions and rootstock variety.…”
supporting
confidence: 91%
“…The gas exchange constitutes an important parameter for evaluation of the photosynthetic activity, which is crucial to determine the adaptation and stability of plants subjected to different environmental adversities, as the variation in photosynthetic rates implies alterations in growth as well as the productivity (Zúñiga et al 2018). We noted that stomatal conductance was negatively affected by water deficiency, both in uninoculated and inoculated red rice plants.…”
Section: Discussionmentioning
confidence: 89%
“…-1.2 MPa; however, they are not sufficient to impair grapevine physiology and metabolism in warm climates ( Romero et al, 2010 ). Previous studies highlighted that plant water status is closely related to leaf gas exchange parameters ( Chaves et al, 2010 ; Zúñiga et al, 2018 ; Villalobos-González et al, 2019 ; Brillante et al, 2020 ). Thus, low values of SWP were related to decreased g s likely because plants subjected to mild to moderate water deficit close their stomata as an early response to water scarcity to diminish water loss and carbon assimilation ( Chaves et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%